Decision Making for Site Selection Using Fuzzy Modeling - Bostanci, Bulent; Zeydan, Mithat; Cete, Mehmet; Demir, Hulya; Karaagac, Abdullah (ASCE-AMER SOC CIVIL ENGINEERS, 2017)
Housing development provides economic growth with location, project ideas, and capital factors. In addition to their own experiences, workers in the field of housing development should consider several criteria when choosing the best locations for residential investments. All of these criteria can be evaluated using fuzzy multicriteria decision-making analyses. In this study, the weights of different evaluation criteria are determined using the fuzzy analytic hierarchy process (FAHP) and fuzzy entropy (FENTROPY) methods. Luxury residential zone-oriented ranking is applied using the fuzzy technique for order preference by the similarity to ideal solution (FTOPSIS) method with weights determined by the FAHP and FENTROPY methods. Performance evaluation for the determination of the best luxury housing is performed by the FTOPSIS method. The criteria weights used in luxury housing site selection are calculated using both objective and subjective techniques. This method was tested for Istanbul, Turkey, and presents an application of fuzzy multicriteria decision-making techniques for area and housing planning problems using several criteria.
Keywords: Site investigation; Knowledge management; Fuzzy analytic hierarchy process; Planning and scheduling; Fuzzy entropy; TOPSIS; AHP; LOCATION; SYSTEM; Engineering; Public Administration; Urban Studies